Kebermanfaatan Zakat Produktif Terhadap Peningkatan Kesejahteraan Mustahiq Lembaga Manajemen Infaq Kantor Surabaya. - Robimadin, Cahya Nugeraha; Cahyono, Hendry (Jurnal Ekonomika dan Bisnis Islam, 2020)
Poverty is a problem in almost every country. One cause of poverty is the low level of welfare in the economic field. Productive zakah is a solution so that economic empowerment can overcome the problem of poverty. The aim of the research is analyze the benefits of productive zakah on improving the welfare of mustahiq. The research method used in this research is qualitative descriptive with fieldbased approach. Information and data resources in this research are Lembaga Manajemen Infaq Surabaya and Mustahiq who received productive zakah. Triangulation (observation, interview and documentation) is used to collect the data. The data in the research is analysed through three step; data reduction, data presentation, and conclusion. The analysis shows that the distribution of productive zakat has various benefits for the mustahiq. While welfare must be unacceptable with material abundance, it must be balanced and oriented to the afterlife.